Representations of Muslim women in selected contemporary Muslim male writings : a new historicist perpective - Mazlen Arepin (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2018)
This thesis provides a detailed study of the representations of Muslim women in the selected contemporary Muslim men's writings. The selected novels were published between 2004 and 2011. The novels studied are Nadeem Aslam's Maps for Lost Lovers (2004), Khaled Hosseini's A Thousand Splendid Suns (2007), Andrea Hirata's The Rainbow Troops (2007), Robin Yassin-Kassab's The Road from Damascus (2008) and Rozlan Mohd Noor's 21 Immortals (2010) and Duke (2011). The study encompasses the contemporary works of Muslim male authors from Asian and Arab backgrounds. It examines the representations of Muslim women as perceived victims of religious, patriarchal and western hegemony before and after the 9/11 events, and the impact of the events within the Muslim male writers' portrayals of Muslim women. The analysis is premised on New Historicism, which considers significant understanding of the authors' background and the time in which the novels were written. The methods of analysis involve a number of approaches such as power and resistance, subversion and containment, authors' backgrounds and perspectives, and contextual factors such as historical, social, political and cultural. The theory is particularly important in the context of considering the circulation of power within the novels and to deliberate on solid historical and cultural explanations that have influenced the authors' writings. The results illustrate that some authors have shown the inclination to validate stereotyped representations of Muslim women as propagated by the Western and patriarchal hegemony. However, the authors' tendency at illustrating such views are balanced by their understanding and empathetic views. The study naturally recognises the authors' attempts to subvert views with regard to patriarchal domination, western stereotyping and conventional opinions against Muslim women in calling the readers' attention to the problems. The diversity and consistency in the authors' perspectives; broadmindedness and discretion would coalesce to reconcile discrimination against Muslim women. The findings also show that Muslim women's transformations are achieved through the power of resistance, which empowers them to take the challenge and redefine their identity. They remain as credible and resilient individuals in their endeavour to subvert patriarchal subordination and western stereotyping.